Effect of Ion Diffusion in Cobalt Molybdenum Bimetallic Sulfide toward Electrocatalytic Water Splitting - Shit, Subhasis; Jang, Wooree; Bolar, Saikat; Murmu, Naresh Chandra; Koo, Hyeyoung; Kuila, Tapas (American Chemical Society, 2019)
The electrocatalyst comprising two different metal atoms is found suitable for overall water splitting in alkaline medium. Hydrothermal synthesis is an extensively used technique for the synthesis of various metal sulfides. Time-dependent diffusion of the constituting ions during hydrothermal synthesis can affect the crystal and electronic structure of the product, which in turn would modulate its electrocatalytic activity. Herein, cobalt molybdenum bimetallic sulfide was prepared via hydrothermal method after varying the duration of reaction. The change in crystal structure, amount of Co-S-Mo moiety, and electronic structure of the synthesized materials were thoroughly investigated using different analytical techniques. These changes modulated the charge transfer at the electrode-electrolyte interface, as evidenced by electrochemical impedance spectroscopy. The Tafel plots for the prepared materials were investigated considering a less explored approach and it was found that different materials facilitated different electrocatalytic pathways. The product obtained after 12 h reaction showed superior catalytic activity in comparison to the products obtained from 4, 8, and 16 h reaction, and it surpassed the overall water splitting activity of the RuO2-Pt/C couple. This study demonstrated the ion diffusion within the bimetallic sulfide during hydrothermal synthesis and change in its electrocatalytic activity due to ion diffusion.